Reading The Public Pulse: Sentiment Analysis of Overclaim Crisis in Indonesia - Husniyah, Estri Khidmatul; Prasetyo, Bambang Dwi; Oktaviani, Fitri Hariana (Universitas Muhammadiyah Surakarta, 2025)
The objective of this study is to analyze public sentiment regarding two local beauty brands in Indonesia, Azarine and The Originote, which were involved in an overclaim crisis on social media. The primary objective of this study is to ascertain the distribution of positive, negative, and neutral sentiments. Additionally, it seeks to elucidate how these sentiment patterns are influenced by the crisis communication strategies implemented by each brand during and after the crisis. A descriptive quantitative method employing sentiment analysis was utilized to collect data from user comments on Instagram and TikTok during the crisis period. The findings indicate that The Originote is more likely to elicit a higher proportion of positive sentiments in comparison to Azarine, a discrepancy attributable to The Originote's strategic emphasis on transparency, acknowledgment of missteps, and dedication to ongoing enhancement. In contrast, Azarine exhibits a diminished prevalence of positive sentiment, signifying a potential for persuasion among audiences who have not yet formed a definitive opinion. These findings indicate that brand response patterns directly influence public sentiment distribution, which in turn affects post-crisis image recovery. This study offers practical implications for local brands to integrate crisis mitigation strategies with proactive public sentiment management. It also opens avenues for further research on the relationship between sentiment intensity and consumer loyalty in the beauty industry.